PENGARUH EKSTRAK SELEDRI TERHADAP PENURUNAN KOLESTEROL TOTAL PADA LANSIA - KASIH, INDAH NOVIA; RAHMAN, SHAHRUL (LP2MTBM MAKARIOZ, 2024)
Cholesterol is a substance needed by the body for the formation of cell membranes in the body, the formation of steroid hormones, and compiling bile salts for fat digestion. Celery contains phytosterols which are phytochemical components that are useful for fighting cholesterol. This study aims to determine the effect of celery extract on reducing cholesterol levels. This research is a quantitative type using a quasi-experimental design with a non-equivalent control group pre and post test design. Subjects amounted to 44 samples taken by purposive sampling method. Data analysis using pair t-test and dependent t-test. The results of the pair t-test test showed p = 0.006 (p <0.05) so that there was a difference between the results of total cholesterol in elderly patients. After conducting research on